Distinct and interdependent functions of three RING proteins regulate recombination during mammalian meiosis - Masaru Ito; Yan Yun; Dhananjaya S. Kulkarni; Sunkyung Lee; Sumit Sandhu; Briana Nuñez; Linya Hu; Kevin Lee; Nelly Lim; Rachel M. Hirota; Rowan Prendergast; Cynthia Huang; et al. (Proceedings of the National Academy of Sciences, 2025)
During meiosis, each pair of homologous chromosomes becomes connected by at least one crossover, as required for accurate segregation, and adjacent crossovers are widely separated thereby limiting total numbers. In coarsening models, this crossover patterning results from nascent recombination sites competing to accrue a limiting pro-crossover RING-domain protein (COR) that diffuses between synapsed chromosomes. Here, we delineate the localization dynamics of three mammalian CORs in the mouse and determine their interdependencies. RNF212, HEI10, and the newest member RNF212B show divergent spatiotemporal dynamics along synapsed chromosomes, including profound differences in spermatocytes and oocytes, that are not easily reconciled by elementary coarsening models. Contrasting mutant phenotypes and genetic requirements indicate that RNF212B, RNF212, and HEI10 play distinct but interdependent functions in regulating meiotic recombination and coordinating the events of meiotic prophase-I by integrating signals from DNA breaks, homolog synapsis, the cell-cycle, and incipient crossover sites.